Model Pendidikan Karakter KH Mas'ud Al-Mudjenar Dalam Pembinaan Perilaku Santri Di Pondok Pesantren Darul Mustaghitsin Lamongan - Moh. Rosyad Ali Ridlo; Nasution Nasution; Aminuddin Kasdi (Universitas Mathla'ul Anwar Banten, 2022)
This study aims to analyze the character education model conducted by KH. Mas'ud Al-Mudjenar through the advice given was able to change the behavior of students at the Darul Mustaghisin Islamic boarding school Lamongan. With the advice given, they are able to foster the behavior of students, who were previously less educated, become students who are educated and have character. The basis of the touch of advice given by Kh. Mas'ud Al-Mudjenar, as exemplified in the behavioristic flow that was expressed by Watson regarding stimulus and response (S-R Psychology).This study uses a qualitative research approach with a descriptive design. Descriptive itself, revealing the factuality of the study and the problem under study. Observations of the character education model conducted by KH. Mas'ud Al-Mudjenar as an effort to foster social behavior of students at the Darul Mustaghisin Islamic boarding school Lamongan has a goal to shape the character of students. Among the models carried out by KH. Mas'ud Al-Mudjenar is like 1). Character education KH. Mas'ud Al-Mudjenar on Religious values, 2). Character education KH. Mas'ud Al-Mudjenar on the values of honesty, 3). Character education KH. Mas'ud Al-Mudjenar on the values of tolerance, 4). Character education KH. Mas'ud Al-Mudjenar on the values of discipline, 5). Character education KH. Mas'ud Al-Mudjenar about hard work, 6). Character education KH. Mas'ud Al-Mudjenar on creative, 7). Character education KH. Mas'ud Al-Mudjenar on independence, 8). Character education KH. Mas'ud Al-Mudjenar democratic, 9). Character education KH. Mas'ud Al-Mudjenar curiosity and 10). Character education KH. Mas'ud Al-Mudjenar responsibility. The whole thing is internalized through the teaching of badongan, madrasah diniyah, collective activities of students and extracurricular activities of students.